Genome size variation and polyploidy in the geographical range of Juniperus sabina L. (Cupressaceae). Issue 2 (3rd April 2019) - Farhat, Perla; Siljak-Yakovlev, Sonja; Adams, Robert P.; Bou Dagher Kharrat, Magda; Robert, Thierry
ABSTRACT: Polyploidy and natural hybridization are considered as two major evolutionary processes involved in plant speciation and diversification. In conifers, natural hybridization has been noticed to be more frequent than polyploidy. Nevertheless, a few cases of polyploidy have been reported in the genus Juniperus . In this genus, a new variety Juniperus sabina var. balkanensis has been postulated to have arisen from an ancient hybridization between the tetraploid species Juniperus thurifera and the diploid species Juniperus sabina var. sabina . The genome size variation and the ploidy level of two J. sabina taxa were estimated by flow cytometry in a panel of 29 populations. All 13 populations of J. sabina var. sabina were diploid, with genome sizes ranging from 22.09 to 25.03 pg/2C, while the 16 populations of J. sabina var. balkanensis were tetraploid, with genome sizes ranging from 41.99 pg to 51.33 pg/2C. These findings open new venues towards the discovering of the polyploidization pathway of J. sabina var. balkanensis and to understand historical and ecological factors that explain its current geographical distribution.